2001
DOI: 10.2337/diabetes.50.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Stimulates Lipolysis in Clonal Pancreatic β-Cells (HIT)

Abstract: Glucagon-like peptide 1 (GLP-1) is the most potent physiological incretin for insulin secretion from the pancreatic ␤-cell, but its mechanism of action has not been established. It interacts with specific cell-surface receptors, generates cAMP, and thereby activates protein kinase A (PKA). Many changes in pancreatic ␤-cell function have been attributed to PKA activation, but the contribution of each one to the secretory response is unknown. We show here for the first time that GLP-1 rapidly released free fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 42 publications
3
63
0
Order By: Relevance
“…While GLP-1 and forskolin, both activators of PKA, have been shown to increase lipolysis in clonal pancreatic beta cells (HIT cells) [37], neither agent enhanced lipolysis in ZF or ZL islets. This finding is in agreement with our study of Hsl wildtype and knockout mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…While GLP-1 and forskolin, both activators of PKA, have been shown to increase lipolysis in clonal pancreatic beta cells (HIT cells) [37], neither agent enhanced lipolysis in ZF or ZL islets. This finding is in agreement with our study of Hsl wildtype and knockout mice [18].…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 has been shown to stimulate fatty acid synthesis from triglyceride stores in both clonal β cell lines and in rat islets. Yaney and colleagues showed that acute treatment of the HIT cell line with GLP-1 (10 nM for 1 hr) increased formation of FFA via a PKAdependent activation of hormone sensitive lipase which led to the rapid breakdown of internal stores of triglycerides (Yaney et al, 2001). Treatment with the acyl synthetase (acyl CoA) inhibitor Triacsin C (which will inhibit FFA conversion to long chain (LC)-acyl CoA) increased the efflux of FFA in response to GLP-1.…”
Section: Glp-1 Effects On β Cell Lipolysismentioning
confidence: 99%
“…These include increasing voltage-sensitive Ca 2ϩ channel opening (48) and Ca 2ϩ influx (49), activating ryanodine receptors in the endoplasmic reticulum (50), stimulating lipolysis (51), and directly acting on the exocytotic machinery (35). Most of these actions are mediated by the protein PKA pathway, but the direct effect on exocytosis is partly PKA-independent (34), being mediated by the cAMP-binding protein cAMP-regulated guanine nucleotide exchange factor II (53).…”
Section: Discussionmentioning
confidence: 99%